The development of technical publishing in Africa - Bgoya, Walter (Technical Centre for Agricultural and Rural Cooperation, 1993)
In an article on publishing in Africa which appeared in the French nespaper Le Monde, the writer commmented that 'in these countries of oral culture, the printed word has difficulty imposing itself'